What information is communicated by radiation therapists to patients during education sessions on the first day of treatment?. (11th September 2018) - Schnitzler, Lena; Smith, Sian K.; Shepherd, Heather L.; Shaw, Joanne M.; Dong, Skye; Turner, Robin M.; Sørensen, Kristine; Dhillon, Haryana M.
Abstract: This study examined the content covered by radiation therapists (RTs) during education sessions; the frequency and types of questions asked by patients; and the relationship between patient characteristics and the number of questions asked. Fifty‐eight education sessions were audio‐recorded and transcribed verbatim. A coding scheme was developed to examine the frequency of topics covered. It comprised 16 topics under four themes: (a) treatment schedule, (b) procedural information, (c) treatment‐related side effects and (d) who will be involved in treatment provision. All education sessions covered information about the treatment plan ( n = 58, 100%), and the majority described procedural information about what happens in the treatment room ( n = 56, 97%). Least information was given about who will be providing treatment. On average, patients asked a mean of 6 questions ( SD = 4.95; range = 0–28). Most frequently asked questions concerned the general treatment (logistics, schedule), accounting for 67% of all questions asked. The least common types of questions were related to the impact of treatment (6%). There were no statistically significant differences in the total number of questions and patient demographics. Patients are provided with most, but not all, of the recommended information. Tailoring of information by RTs was enabled in response to questions asked.